2018
DOI: 10.1177/0748730417754116
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-natural Approach for Studying Seasonal Diapause inDrosophila melanogasterReveals Robust Photoperiodicity

Abstract: The fruit fly Drosophila melanogaster survives thermally stressful conditions in a state of reproductive dormancy (diapause), manifested by reduced metabolic activity and arrested ovarian development in females. Unlike insects that rely primarily on photoperiodic stimuli to initiate the diapause program, in this species dormancy is regulated by low temperature and enhanced by shorter photoperiods. Overwintering phenotypes are usually studied under simple laboratory conditions, where animals are exposed to rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 43 publications
0
17
2
Order By: Relevance
“…However, some recent studies do observe short-day photoperiodic responses in diapause [88, 96]. One study suggested that light conditions which mimic the natural daily variation of solar radiation can in fact generate a photoperiodic response [97]. In our study, short days under rectangular light cycles with standard white LED light did not increase diapause induction.…”
Section: Discussioncontrasting
confidence: 52%
“…However, some recent studies do observe short-day photoperiodic responses in diapause [88, 96]. One study suggested that light conditions which mimic the natural daily variation of solar radiation can in fact generate a photoperiodic response [97]. In our study, short days under rectangular light cycles with standard white LED light did not increase diapause induction.…”
Section: Discussioncontrasting
confidence: 52%
“…Whether D. melanogaster represents a suitable model to study diapause has been under debate. However, recent studies suggest that the photoperiodic component of D. melanogaster might be more robust than previously described (18,19). We found that newly emerged females reared at 10°C for 28 d exhibit significantly smaller ovaries when exposed to short photoperiod (SP 8L:16D, where L denotes hours of light and D denotes hours of dark) compared to long photoperiod (LP 16L:8D).…”
mentioning
confidence: 46%
“…Whether D. melanogaster represents a suitable model to study diapause has been under debate. However recent studies suggest that the photoperiodic component of D. melanogaster might be more robust than previously described (18, 19). We found that newly emerged females reared at 10°C for 28 days, exhibit significantly smaller ovaries when exposed to short photoperiod (SP 8L:16D) compared to long photoperiod (LP 16L:8D).…”
Section: Introductionmentioning
confidence: 77%